2016
DOI: 10.1371/journal.pone.0160857
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Sex-Specific Transgenerational Effects of a High Fat Diet in Drosophila melanogaster

Abstract: An organism's phenotype is the product of its environment and genotype, but an ancestor’s environment can also be a contributing factor. The recent increase in caloric intake and decrease in physical activity of developed nations' populations is contributing to deteriorating health and making the study of the longer term impacts of a changing lifestyle a priority. The dietary habits of ancestors have been shown to affect phenotype in several organisms, including humans, mice, and the fruit fly. Whether the anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 51 publications
3
53
0
Order By: Relevance
“…Importantly, these effects were seen even with full outbreeding using unexposed C57BL/6J mice, compared with transgenerational studies where treated animals are bred to each other. Although differences by sex in F3 consequences are certainly recognized (Dew-Budd et al 2016;Zizzari et al 2016), the contribution of lineage transfer in relation to sex, and potential dynamic changes in response to ongoing environmental conditions, have received far less attention (Burggren 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these effects were seen even with full outbreeding using unexposed C57BL/6J mice, compared with transgenerational studies where treated animals are bred to each other. Although differences by sex in F3 consequences are certainly recognized (Dew-Budd et al 2016;Zizzari et al 2016), the contribution of lineage transfer in relation to sex, and potential dynamic changes in response to ongoing environmental conditions, have received far less attention (Burggren 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies documenting ancestral dietary modifications on offspring response only focus on a single extreme modification (e.g. a high-fat diet, a high-sugar diet, or a protein-restricted diet) (Zambrano et al, 2005, Benyshek et al, 2006, Dunn and Bale, 2011, Matzkin et al, 2013, Dew-Budd et al, 2016, Ost et al, 2014, Hoile et al, 2011). To better understand whether varying concentrations of the same ancestral dietary modification can lead to similar transgenerational responses, we compared the transgenerational responses of the three ancestral dietary sugar concentrations in flies.…”
Section: Discussionmentioning
confidence: 99%
“…While some evidence exists for the transmission of stable effects in the literature (Remy, 2010, Rechavi et al, 2014, Ashe et al, 2012), the fluctuating responses found in our study generally do not appear to match with these findings. Conversely, delayed and diminishing responses are quite common for transgenerational studies (J Marshall and Uller, 2007, Gluckman et al, 2005, Nystrand et al, 2016, Xia and De Belle, 2016, Dew-Budd et al, 2016, Buescher et al, 2013, Dunn and Bale, 2011, Pentinat et al, 2010, Franklin et al, 2010, Walsh et al, 2015). Unfortunately, these aforementioned interpretations are frequently based on studies with short-time scales and single-exposure changes, limiting the scope of inference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduction also requires tight control of lipid homeostasis. Although females must increase oocyte and whole-animal lipogenesis to support the production of offspring (Sieber and Spradling, 2015), morbid maternal obesity adversely affects egg size, glycogen and TAG content, adult mass and gene expression in offspring and even in the F2 generation (Buescher et al, 2013;Dew-Budd et al, 2016;Matzkin et al, 2013). Highly obesogenic diets reduce fecundity (Brookheart et al, 2017;Matzkin et al, 2013Matzkin et al, , 2011 as does genetically induced obesity (Palu et al, 2017).…”
Section: Perspectivesmentioning
confidence: 99%